Slow Moving Items Inventory Policy Under Poisson Distribution Demand Design In Yogyakarta Central Warehouse Of Pt. Kereta Api Indonesia For Minimizing Total Relevant Cost Inventory Using Continuous Review (s,q) Method - Bernanda Tricahyo; Ari Yanuar Ridwan; Meldi Rendra (eProceedings of Engineering, 2016)
PT. Kereta Api Indonesia (Persero), hereafter PT KAI (Persero) is the biggest railway industry in Indonesia, in terms of inventory, the company must be dealing slow moving item. As of 2015 the slow moving value worth IDR 70 billion and practically reached 0.8 million items. The suggested model continuous review (s,Q) under poisson distribution data over lead time was performed in one of PT KAI’s central warehouses by using two- stage spare parts classification, Yogyakarta Central Warehouse (GPYK) that determines the optimal order size and reorder point to reduce annual total relevant cost (TRC) inventory along with CSL or cycle service level and fill rate. The percentage of reduced annual six SKUs TRC is up to 52% from existing TRC or gained to be exact IDR 4.1 million of savings, resulting the average percentage of CSL and fill rate as much as 98%. Keywords: Slow Moving Item, VED Classification, Poisson Distribution, Continuous Review (s,Q), Cycle Service Level, Fill Rate, Total Relevant Cost TRC.